Perspektif Mahasiswa terhadap Pemanfaatan Artificial Intelligence di Sekolah Tinggi Teologi Gereja Kalimantan Evangelis - Rena Berkatni (Jurnal Teologi Pambelum, 2026)
Advances in Artificial Intelligence (AI) present both opportunities and challenges for theological education. This study aims to describe students’ perspectives on the use of AI at the Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), including its benefits, risks, and ethical and theological implications. The study employed a qualitative approach using a case study design involving seven students selected through purposive sampling. Data were collected via a Google Form containing open-ended questions, observations, and document analysis, and were then analyzed using the interactive model developed by Miles, Huberman, and Saldaña. The results indicate that students view AI as a tool that can assist with learning, information retrieval, assignment evaluation, research, and academic work. However, the implementation of AI at STT GKE has not yet been fully integrated, as many of the services currently in use are limited to information technology and multimedia. This study recommends the development of guidelines for AI use and the promotion of AI literacy that integrates academic, ethical, and theological aspects.